A case report of disseminated cysticercosis in Bali, Indonesia - A.A Raka Sudewi; Toni Wandra; Oka Adnyana; NFN Moestikaningsih; A A.B.N. Nuartha; Yasuhito Sako; Kazuhiro Nakaya; Akira Ito (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2013)
Abstract. We reported the case of a 36-year-old Balinese man who disseminated cysticercosis, presented neuro-, subcutaneous- and oral-cysticercosis. Diagnosis of it was based on anamnesis, clinical examination including CT Scan, histopathological and serological examinations. The patient visited outpatient clinic of Sanglah Denpasar Hospital in Bali, in June 2003 with two subcutaneous nodules in the body. Serological examinations (ELISA and immnunoblot) used both purified glycoproteins and chimeric recombinant antigen were positive. The two subcutaneous nodules disappeared after treatment with albendazole. In January 2004, the patient presented neuro-, and oral-cysticercosis. CT Scan showed multiple active lesions in the brain. During the treatment with 800 mg albendazole daily during for one month. The side effects of it such as nausea and vomit were found in that patient. Antibody responses in ELISA and immnunoblot were still positive and follow up CT scan in May 2004, it showed that very similar figures as previously. Repeated treatment with 400mg albendazole daily for one and half month was applied. Antibody responses became low, and CT scan in March 2006 did not show any active cysts but only calcified lesions.